2018
DOI: 10.1039/c8ta01192c
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature SnO2-modified TiO2 yields record efficiency for normal planar perovskite solar modules

Abstract: SnO2-modified TiO2 films fabricated at low temperatures toward stable, high-efficiency and less-hysteresis planar perovskite solar modules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(49 citation statements)
references
References 66 publications
0
49
0
Order By: Relevance
“…In a low-temperature anneal at 120 °C, a TiO 2 layer can be also formed based on aqueous TiCl 4 . Although the resultant TiO 2 /SnO 2 composite can contribute a maximum PCE of 21.27% [23], this PCE is still restricted by the amorphous phase of TiO 2 here [17]. Therefore, it is still deserved to adjust the Ti component on its lattice phase and nanostructure for gaining higher PCE of device.…”
Section: Introductionmentioning
confidence: 99%
“…In a low-temperature anneal at 120 °C, a TiO 2 layer can be also formed based on aqueous TiCl 4 . Although the resultant TiO 2 /SnO 2 composite can contribute a maximum PCE of 21.27% [23], this PCE is still restricted by the amorphous phase of TiO 2 here [17]. Therefore, it is still deserved to adjust the Ti component on its lattice phase and nanostructure for gaining higher PCE of device.…”
Section: Introductionmentioning
confidence: 99%
“…To identify the SnO 2 ‐induced impact on TiO 2 , the performance of PSCs based on the different ETLs was investigated, which clarified that the SnO 2 on TiO 2 had improved the photovoltaic performance dramatically. Ding et al also used SnO 2 to treat TiO 2 films . The preparation process of ETL was described as following.…”
Section: Enhancing Performance Of Pscsmentioning
confidence: 99%
“…The lower‐temperature annealing also makes it compatible with the fabrication process of flexible PSCs. Until now, the highest PCE for PSCs based on SnO 2 has reached more than 21%, which is the highest PCE for the planar structure PSCs . The development of SnO 2 ‐based PSCs is shown in Figure a.…”
Section: Introductionmentioning
confidence: 98%
“…[33] Ding et al reported a three-step CBD process, taking several hours, to coat the SnO 2 -based ESL, and they fabricated a device through the gas-pumping method with a PCE of 21.96 %. [34] Although the use of the CBD methods to deposit SnO 2 as the ESL in PSCs has achieved success, it is a very timeconsuming process for suppressing self-aggregation, which counters the methodological advantages of the CBD process and limits its versatile application. Additionally, it is still not understood why the J-V hysteresis is alleviated in the charge transport dynamics of SnO 2 -based PSCs but not in the TiO 2based PSCs.…”
Section: Introductionmentioning
confidence: 99%